2019
DOI: 10.1093/ptep/ptz062
|View full text |Cite
|
Sign up to set email alerts
|

Null geodesics and repulsive behavior of gravity in $(2+1)$D massive gravity

Abstract: We study the null geodesics in a static circularly symmetric (SCS) black hole spacetime which is a solution in the (2 + 1)-dimensional massive gravity proposed by Bergshoeff, Hohm and Townsend (BHT massive gravity). We obtain analytic solutions for the null geodesic equation in the SCS black hole background and find the explicit form of deflection angles. We see that for various values of the impact parameter, the deflection angle can be positive, negative or even zero in this black hole spacetime. The negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…An interesting phenomenon in the b > 0 case was analyzed in [12], namely that due to the hair parameter a repulsive behavior of the black hole on null geodesics was observed. This also appears in our analysis, although in a subtle form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting phenomenon in the b > 0 case was analyzed in [12], namely that due to the hair parameter a repulsive behavior of the black hole on null geodesics was observed. This also appears in our analysis, although in a subtle form.…”
Section: Discussionmentioning
confidence: 99%
“…In the null case the equations of motion can be integrated analytically, which has been done in [12].…”
Section: Circular Geodesicsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) It acts, through an entanglement bond, between the real protons orbiting in proton star, on the one hand, and the electrons that most likely revolve in the innermost band of the space surrounding the proton star, in which case it is attractive-repulsive at same time. After all in some recent researches, in particular see references [9] and [10], it has been shown that the possible trajectories of photons and of particles inside and around the black hole are compatible with a repulsive behavior of gravity. In the reference [11], then, a repulsive gravity was shown within the black hole even in the Stueckelberg Quantum formalism;…”
Section:  513 -The Reason Of Non-decreasing Velocity Of Stars and Of Electronsmentioning
confidence: 99%
“…Studying the geodesic equations have been extended to F(R) gravity and conformal gravity in BTZ and GMGHS (Gibbons-Maeda-Garfinkle-Horowitz-Strominger) black holes [107][108][109][110][111], regular and modified Hayward black holes [112,113], charged dilatonic black holes [114], the singly spinning and (charged) doubly spinning black ring [115,116], brane-world black hole [117], (rotating) black string [118], Schwarzschild, and Kerr pierced by black string spacetimes [119,120]. Moreover, regarding three dimensional spacetime, the stability and existence of circular geodesics in a family of asymptotically AdS black holes in new massive gravity theory [121] and the null geodesics in a static circularly symmetric black hole spacetime [122] have been investigated before. Furthermore, in Ref.…”
Section: Introductionmentioning
confidence: 99%